Examining the Internship Curriculum in Acquiring Teaching Abilities (European Journal of Behavioral Sciences, 2018)
Considering the importance of experience in learning each topic and its importance in becoming professional actualize knowledge, today, a particular focus is done on the more precise formation of internship courses during education. One of the most sensitive of these educational courses is related to teacher training. Hence, in this article, titled the study of the internship curriculum in acquiring the teaching abilities, we express the characteristics of the teacher required from different sources and the internship needs in all professions as well as the importance of this curriculum in teacher’s training and the relationship of this curriculum in the acquisition of teaching competences and we study the implementation of this curriculum at the University of Farhangian. As well as we compare the standards of this curriculum in the teacher training of advanced countries and study the shortcomings and positive points, as well as the view of the students of Shahid Ayat Najaf Abad Center (Farhangian University) about this curriculum. The result of the study shows that this curriculum is effective in acquiring the teaching competencies, but it requires reforms in line with the criteria of update knowledge and the national transformation document to overlap the desired criteria.